2021
DOI: 10.11648/j.cajph.20210702.12
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Accept a COVID-19 Vaccine in Nigeria: A Population-based Cross-sectional Study

Abstract: Background: The study assessed the intention to accept a future COVID-19 vaccine in Nigeria and associated factors. Materials and Methods: Between July 2020 and August 2020, a cross-sectional study was conducted using an online questionnaire that captured demographic data, risk perception, trust in government and public health authorities and willingness to accept a future COVID-19 vaccine. Data were analyzed using Statistical Package for Social Science version 21.0, Chi-square and logistic regression were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 14 publications
6
38
0
Order By: Relevance
“…This is expected because age is one of the major factors affecting COVID-19 infection, with elderly people having weaker immune systems and thus at a higher risk of infection. A similar finding had been reported in some previous studies [15,[18][19][20][21]. Furthermore, the "currently working" variable significantly increased the probability of willingness to be vaccinated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is expected because age is one of the major factors affecting COVID-19 infection, with elderly people having weaker immune systems and thus at a higher risk of infection. A similar finding had been reported in some previous studies [15,[18][19][20][21]. Furthermore, the "currently working" variable significantly increased the probability of willingness to be vaccinated.…”
Section: Discussionsupporting
confidence: 90%
“…This result reveals the gender factor that can impact efforts by government in addressing COVID-19 in Ethiopia. In some previous studies [15,19,21], gender was found to influence decisions around the COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Concerning to the associated factors, from a total of 45 studies included in the present systematic review, 39 of the studies have assessed the associated factors with individuals' willingness of receiving COVID-19 vaccine. From 39 studies assessed the associated factors with willingness of receiving COVID-19 vaccine, some of the studies have reported that sociodemographic factors such as age, 32,[35][36][37]39,43,48,49,56,58,60,61,65,68,69,72,73 educational status, [30][31][32]36,43,72 gender, 32,[35][36][37]47,48,52,53,55,[59][60][61]65,68,69,[71][72][73][74] income, 36,54,61 residency, 36,60,74 occupation,…”
Section: Discussionmentioning
confidence: 99%
“…The study design of all these studies were cross-sectional. Nine studies were done in the United States, [30][31][32][33][34][35][36][37][38] nine studies were done in China, [39][40][41][42][43][44][45][46][47] one study was done in Australia, 48 four studies were done in Saudi Arabia, [49][50][51][52] one study was done in Kuwait, 53 one study was done in England, 54 one study was done in Congo, 55 one study was done in Greece, 56 two studies were done in UK, 57,58 one study was done in Malaysia, 59 two studies were done in Japan, 60,61 one study was done in Israel, 62 one study was done in Bangladesh, 63 one study was done in Jordan, 64 one study was done in Iran, 65 one study was done in Italy, 66 one study was done in Ethiopia, 67 two studies were done in France, 68,69 one study was done in Vietnam, 70 one study was done in Uganda, 71 one study was done in Pakistan, 72 one study was done in Nigeria, 73 an...…”
Section: Features Of the Included Studiesmentioning
confidence: 99%